Validity And Practicality Of Student Worksheet Integrated With Problem Based Learning In Meteorology And Climatology Subjects - Muhammad Arif; Alexander Syam; Veni (Indonesian Journal of Glasial Geography, 2024)
Meteorology and climatology subject requires appropriate teaching materials that are integrated with problem based learning. This type of research is R&D with the focus of research being the validation and practicality of student worksheets. The data collection instrument used was a questionnaire. Validation was carried out by three geography education lecturers as experts by filling out questionnaires to assess student worksheets and through discussions to obtain suggestions for improvement. The validation of student worksheets carried out includes four assessment indicators namely content, construct, language, and graph validation. The practicality of student worksheets is filled in by lecturers and students as users by filling in five practicality indicators. The results showed (1) student worksheets integrated with the problem-based learning model were in the valid category for use, (2) student worksheets were in the practical category which meant the worksheets that were developed were easy to understand, easy to implement, efficient in cost and time, and easy to find the tools and materials needed for learning.